The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1108/bjm-03-2022-0112
|View full text |Cite
|
Sign up to set email alerts
|

Moderating role of perceived work addiction of managers in the relationship between employees' perfectionism and work addiction: a trait activation theory perspective

Abstract: PurposeEarlier authors suggested that a combination of different factors leads to the development of work addiction, hereby indicating that no single perspective is enough to fully understand this phenomenon. Hence, the aim of this study was to examine the moderating role of perceived work addiction of managers in the relationship between employees' perfectionism and work addiction.Design/methodology/approachThe present cross-sectional study was conducted on a convenience sample of 964 workers from different o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
(128 reference statements)
0
5
0
Order By: Relevance
“…While most of the previous studies focused on the consequences of work addiction for an individual itself, we shed light on the role of addicted people in explaining work addiction of others. Moreover, although several studies (e.g., Morkevičiūtė & Endriulaitienė, 2022a, 2022b; Chamberlin & Zhang, 2009; Kravina et al ., 2014) investigated the importance of managers' or parents' addictive behaviors for the employees' well‐being, attitudes and behaviors at work, no research comparing the role of both parents' and managers' work addiction within the context of employee work addiction has been carried out yet.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While most of the previous studies focused on the consequences of work addiction for an individual itself, we shed light on the role of addicted people in explaining work addiction of others. Moreover, although several studies (e.g., Morkevičiūtė & Endriulaitienė, 2022a, 2022b; Chamberlin & Zhang, 2009; Kravina et al ., 2014) investigated the importance of managers' or parents' addictive behaviors for the employees' well‐being, attitudes and behaviors at work, no research comparing the role of both parents' and managers' work addiction within the context of employee work addiction has been carried out yet.…”
Section: Discussionmentioning
confidence: 99%
“…A prominent perspective on work addiction – socio‐cultural perspective – suggested that work addiction is a product of social and cultural experiences that individuals go through a lifespan (Ng, Sorensen & Feldman, 2007). Work‐related behavior of significant/authoritative others in the family and in the workplace can be attributed to those socio‐cultural factors which are most frequently held responsible for working behaviors of employees (Morkevičiūtė & Endriulaitienė, 2022a; Kim et al ., 2020; Kravina et al ., 2014; Robinson, 2000).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, other-oriented perfectionism in leaders was found to be associated with monitoring behaviors and highlighted as a barrier to building trusting relationships (Otto et al, 2021). Other results investigated the effects of the interaction between managers' perfectionism and employees' perfectionism on work addiction, revealing that employees' socially prescribed perfectionism and work addiction was strongest when a manager was perceived to be addicted to work (Morkevičiûtė and Endriulaitienė, 2022).…”
Section: Introductionmentioning
confidence: 96%